2018
DOI: 10.1038/s41420-018-0110-1
|View full text |Cite|
|
Sign up to set email alerts
|

Lon protease inactivation in Drosophila causes unfolded protein stress and inhibition of mitochondrial translation

Abstract: Mitochondrial dysfunction is a frequent participant in common diseases and a principal suspect in aging. To combat mitochondrial dysfunction, eukaryotes have evolved a large repertoire of quality control mechanisms. One such mechanism involves the selective degradation of damaged or misfolded mitochondrial proteins by mitochondrial resident proteases, including proteases of the ATPase Associated with diverse cellular Activities (AAA+) family. The importance of the AAA+ family of mitochondrial proteases is exem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 64 publications
1
45
3
Order By: Relevance
“…In addition, a longevity model system in mice showed that an increase in the level of mitochondrial PQC components, here mtHsp60 and Lon were analyzed, correlated with an increased life span. On the other hand, Lon knockdown experiments in Drosophila flies confirmed an overall shortened lifespan, and a reduced respiration efficiency that was even more pronounced in older flies [51]. Taken together, these observations generally support the important role of mitochondrial fitness on cellular aging processes.…”
Section: Role In Agingsupporting
confidence: 59%
See 1 more Smart Citation
“…In addition, a longevity model system in mice showed that an increase in the level of mitochondrial PQC components, here mtHsp60 and Lon were analyzed, correlated with an increased life span. On the other hand, Lon knockdown experiments in Drosophila flies confirmed an overall shortened lifespan, and a reduced respiration efficiency that was even more pronounced in older flies [51]. Taken together, these observations generally support the important role of mitochondrial fitness on cellular aging processes.…”
Section: Role In Agingsupporting
confidence: 59%
“…However, a genetic depletion study of Lon in Drosophila flies found a moderate decrease of mitochondrial functions, including some reduction of respiration (but only complex I-and IV-mediated) and some decrease of mitochondrial translation. Both observations correlate well because a decrease in the biogenesis of mitochondrially encoded proteins (including folding and/or assembly into active enzyme complexes) will directly affect the oxidative phosphorylation efficiency [51,52].…”
Section: Role In Gene Expressionmentioning
confidence: 62%
“…We and others have previously observed increased ATF4 and CHOP in mouse models with impaired mitochondrial translation (Rackham et al , ; Seiferling et al , ; Perks et al , ), and impaired mitochondrial translation can induce mtUPR in worms and mammalian cell culture (Houtkooper et al , ). In contrast, loss of the Lon protease in flies activates mtUPR and inhibits mitochondrial translation (Pareek et al , ) and the downstream targets of mtUPR include mitochondrial translation in mammalian cell culture (Münch & Harper, ). These observations highlight the distinct systems of nuclear‐mitochondrial signaling in mammals and the need for further studies to understand how mitochondrial stress response programs bifurcate under different stresses.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously observed increased ATF4 and CHOP in mouse models with impaired mitochondrial translation (Rackham et al, 2016;Seiferling et al, 2016;Perks et al, 2018), and impaired mitochondrial translation can induce mtUPR in worms and mammalian cell culture (Houtkooper et al, 2013). In contrast, loss of the Lon protease in flies activates mtUPR and inhibits mitochondrial translation (Pareek et al, 2018) ◀ Figure 6. Hyper-accurate mitochondrial mistranslation reduces mitochondrial respiration and results in a progressive dilated cardiomyopathy.…”
Section: Of 19mentioning
confidence: 95%
“…Upon entering the body, the NPs are recognized as external units and are removed from the blood circulation. After the chitosan-based NPs enter in the blood system the following events occur: (1) fast formation of PC by association of NPs with plasmatic proteins; (2) rearrangement of proteins in “hard” and “soft” corona layers; (3) possible activation or inactivation on metabolic enzyme cascades; (4) induction of immune response and induction of recognition process of PC by immune cells; (5) initiation of macrophage uptake of NPs coated with PC and their elimination from the bloodstream; (6) subsequent accumulation of NPs coated with PC in some specialized cells (excluding macrophages); (7) eventually initiation of some signaling pathways and apoptosis processes [ 75 , 76 , 77 ].…”
Section: The Fate Of the Nps-pcmentioning
confidence: 99%